Murder Crimes in Palestine: Factorial Study - Arar, Rashid mohammed; Khaled, Ahmad Ali; Abdullah, Tayseer Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to discover the factors and dimensions of murder crimes in Palestine (the West Bank, the Gaza Strip, Jerusalem, and the occupied Palestinian interior), using the analytical descriptive method and through the Google Survey program, the study was administered on a random sample of (340) individuals, the majority of them are those who have completed their university studies, (140) males, and (200) females, their average age is (33.91). The results, via Factor Analysis, indicated that the dimensions of the questionnaire used, and the component dimensions of the murders, were tested, and validity and reliability were calculated via construct validity, internal consistency, Cronbach Alpha reliability coefficients, Split-half reliability, and exploratory factor analysis, which indicated the presence of six factors for the murders explained (51%) of the total variance. The factors of the murders were a factor of the weakness of the law enforcement agencies, followed by abnormal behavior, Occupation, psychological disorders and social problems, socialization, and the factor of order and congestion. The study recommended the importance of being guided by law enforcement agencies. To review the means of confronting the phenomenon of homicide.
Keywords: Homicide; Murder; Factor analysis; Palestine